2003
DOI: 10.4049/jimmunol.170.5.2540
|View full text |Cite
|
Sign up to set email alerts
|

NKT Cells Provide Help for Dendritic Cell-Dependent Priming of MHC Class I-Restricted CD8+ T Cells In Vivo

Abstract: Dendritic cells (DC) are potent APCs for naive T cells in vivo. This is evident by inducing T cell responses through adoptive DC transfer. Priming specific CTL responses in vivo often requires “help”. We study alternative sources of help in DC-dependent priming of MHC class I-restricted CTL. Priming an anti-viral CTL response in naive B6 mice by adoptive transfer of antigenic peptide-pulsed DC required CD4+ T cell help. CTL priming was facilitated by providing MHC class II-dependent specific help. Furthermore,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
105
2
1

Year Published

2003
2003
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 115 publications
(111 citation statements)
references
References 75 publications
3
105
2
1
Order By: Relevance
“…In mice injected with DCs only, 9% (p Ͻ 0.01) of the mice were tumor-free after 12 wk, ruling out the possibility that tumor rejection was solely due to NK cell expansion, which can be induced by DCs (37)(38)(39) or to immunity in response to culture medium proteins presented by DCs. It has been shown that DCs cultured in the presence of FCS are capable of inducing CD4 ϩ T cell help (40,41) and to prime CTLs more efficiently than DCs cultured in FCS-free conditions (40). Therefore, the presence of FCS-derived peptides loaded onto the DCs might have contributed to the observed antitumor response.…”
Section: Dcs Loaded With Apoptotic B16 Cells Induce Specific Resistanmentioning
confidence: 99%
See 1 more Smart Citation
“…In mice injected with DCs only, 9% (p Ͻ 0.01) of the mice were tumor-free after 12 wk, ruling out the possibility that tumor rejection was solely due to NK cell expansion, which can be induced by DCs (37)(38)(39) or to immunity in response to culture medium proteins presented by DCs. It has been shown that DCs cultured in the presence of FCS are capable of inducing CD4 ϩ T cell help (40,41) and to prime CTLs more efficiently than DCs cultured in FCS-free conditions (40). Therefore, the presence of FCS-derived peptides loaded onto the DCs might have contributed to the observed antitumor response.…”
Section: Dcs Loaded With Apoptotic B16 Cells Induce Specific Resistanmentioning
confidence: 99%
“…5A). Although these assays were performed using mouse serum, the DCs used as APCs had been cultured in 10% FCS, and the presence of FCS-derived peptides could explain the control CD4 ϩ T cell response observed against DC-OVA or DCs alone (40,41). T cells from control nonvaccinated mice made Ͻ30 pg/ml of IFN-␥ with or without challenge (data not shown).…”
Section: Dcs Charged With Apoptotic B16 Efficiently Prime Both Cd4 ϩ mentioning
confidence: 99%
“…41,45,49,54 -56,58,61 By responding to infectious or other challenges prior to conventional adaptive T cells, CD1d-reactive T cells could have the potential to influence the course of local and systemic bias of immune responses. Activated CD1d-reactive T cells can stimulate NK cells 59 and cytotoxic T lymphocytes, 23,24,62 actions dependent in part on the ability of the CD1d-reactive T cells to produce IFN-␥. In addition to the possible role of CD1d-reactive T-cell-produced cytokines as facilitators of immune responses, IFN-␥ and other cytokines may play a role in the clearance of pathogens, especially viral pathogens.…”
Section: Roles Of Cd1d-reactive Nkt Cellsmentioning
confidence: 99%
“…2,19,20 NKT cell activation and IFN-␥ production are markedly enhanced by DC-produced IL-12, with an increase in the IL-12 receptor on activated NKT cells. 15,21,22 Conversely, invariant NKT cells also interact with ␣Gal-Cer-loaded DCs to enhance CD4 ϩ and CD8 ϩ T-cell responses 16,17,23,24 and with B cells to provide help for antibody production. 25 However, ␣Galcer is not a physiological antigen, and it is not yet clear whether physiological NKT-DC interactions are mediated by specific CD1d-presented antigens or are antigen independent.…”
mentioning
confidence: 99%
“…Indeed, according to some reports NKT cells represent potent helper cells for DC-dependent CTL priming. 50 …”
Section: Discussionmentioning
confidence: 99%